?-importin Tnpo-SR promotes germline stem cell maintenance and oocyte differentiation in female Drosophila. - Beachum, A.N.; Hinnant, T.D.; Williams, A.E.; Powell, A.M.; Ables, E.T. (Developmental Biology, 2023)
Germ cell development requires interplay between factors that balance cell fate and division. Early in their development, germ cells in many organisms divide mitotically with incomplete cytokinesis. Key regulatory events then lead to the specification of mature gametes, marked by the switch to a meiotic cell cycle program. Though the regulation of germ cell proliferation and meiosis are well understood, how these events are coordinated during development remains incompletely described. Originally characterized in their role as nucleo-cytoplasmic shuttling proteins, ?-importins exhibit diverse functions during male and female gametogenesis. Here, we describe novel, distinct roles for the ?-importin, Transportin-Serine/Arginine rich (Tnpo-SR), as a regulator of the mitosis to meiosis transition in the Drosophila ovary. We find that Tnpo-SR is necessary for germline stem cell (GSC) establishment and self-renewal, likely by controlling the response of GSCs to bone morphogenetic proteins. Depletion of Tnpo-SR results in germ cell counting defects and loss of oocyte identity. We show that in the absence of Tnpo-SR, proteins typically suppressed in germ cells when they exit mitosis fail to be down-regulated, and oocyte-specific factors fail to accumulate. Together, these findings provide new insight into the balance between germ cell division and differentiation and identify novel roles for ?-importins in germ cell development.